Effects of on-farm and traditional hatching on welfare, health, and performance of broiler chickens - Ingrid C. de Jong; Theo van Hattum; Johan W. van Riel; Kris De Baere; Ine Kempen; Sofie Cardinaels; Henk Gunnink (Poultry Science, 2020)
In on-farm hatching systems, eggs that have been incubated for 18 D are transported to the broiler farm. After hatching around day 21, the chicks have immediate access to feed and water. By contrast, traditionally hatched chicks are in early life exposed to dust and pathogens in the hatcher, handling procedures, and transport and remain without feed and water until they have arrived on the farm 1 to 3 D after hatching. We compared welfare and performance of on-farm hatched (OH) and traditionally hatched control (C) Ross 308 broiler chickens from day 0 to 40, housed under semicommercial conditions. The experiment included 3 production cycles in 4 rooms, with each room containing 1 OH and 1 C pen with 1,150 chickens in each pen. Per cycle, C and OH chicks were from the same batch of eggs of 1 parent stock flock. Day-old chick quality was worse for OH than C chickens (hock and navel score; P < 0.05). On-farm hatched chickens were heavier than C chickens until day 21 of age (P < 0.05). Total mortality was significantly lower in OH compared with C pens (P < 0.05). A tendency for lower footpad dermatitis scores was found in OH pens compared with C pens (P < 0.10), probably because of the dryer litter in OH than C pens (P < 0.05). No differences between treatments were found in gait, hock burn, cleanliness, and injury scores, and no or only minor, short lasting differences were found in pathology and intestinal histology. In conclusion, the present study showed that on-farm hatching may be beneficial for broiler welfare, as it reduced total mortality and resulted in dryer litter which is known to be beneficial for reducing footpad dermatitis.